Višina pokojnine - Papež, Marijan (Delavci in delodajalci, 2015)
In this article the author gives the trends of pension rate movements since the implementation of the first independent and integral pension and disability insurance system in Slovenia, which took effect on 1 April 1992, and until the current Pension and Disability Insurance Act, in place since 1 January 2013 (ZPIZ-2). So far Slovenia has seen three pension reforms, starting with the first Pension and Disability Insurance Act of 1 April 1992 (ZPIZ) and followed by the Pension and Disability Insurance Act of 1 January 2000 (ZPIZ-1). All three reforms aimed to provide long-term stability of the system, resulting in changes to pension rates. The most radical changes in terms of pension rates (their reduction) were introduced by ZPIZ-1. Significant, though not as radical, were changes affecting pension rates where additional income had been paid simultaneously.
Keywords: plače; pokojnine; pokojninsko zavarovanje; Slovenija; starostna meja (pokojninsko zavarovanje)